Outcomes of beta blocker use in advanced hepatocellular carcinoma treated with immune checkpoint inhibitors - Wu, Y. Linda; van Hyfte, Grace; Özbek, Umut; Reincke, Marlene; Gampa, Anuhya; Mohamed, Yehia I.; Nishida, Naoshi; Wietharn, Brooke; Amara, Suneetha; Lee, Pei-Chang; Scheiner, Bernhard; Balcar, Lorenz; et al. (Frontiers in Oncology, 2023)
Background: In patients with cirrhosis, portal hypertension increases intestinal permeability, dysbiosis, and bacterial translocation, promoting an inflammatory state that can lead to the progression of liver disease and development of hepatocellular carcinoma (HCC). We aimed to investigate whether beta blockers (BBs), which can mediate portal hypertension, conferred survival benefits in patients treated with immune checkpoint inhibitors (ICIs). Methods: We conducted a retrospective, observational study of 578 patients with unresectable HCC treated with ICI from 2017 to 2019 at 13 institutions across three continents. BB use was defined as exposure to BBs at any time during ICI therapy. The primary objective was to assess the association of BB exposure with overall survival (OS). Secondary objectives were to evaluate the association of BB use with progression-free survival (PFS) and objective response rate (ORR) according to RECIST 1.1 criteria. Results: In our study cohort, 203 (35%) patients used BBs at any point during ICI therapy. Of these, 51% were taking a nonselective BB. BB use was not significantly correlated with OS (hazard ratio [HR] 1.12, 95% CI 0.9-1.39, P = 0.298), PFS (HR 1.02, 95% CI 0.83-1.26, P = 0.844) or ORR (odds ratio [OR] 0.84, 95% CI 0.54-1.31, P = 0.451) in univariate or multivariate analyses. BB use was also not associated with incidence of adverse events (OR 1.38, 95% CI 0.96-1.97, P = 0.079). Specifically, nonselective BB use was not correlated with OS (HR 0.94, 95% CI 0.66-1.33, P = 0.721), PFS (HR 0.92, 0.66-1.29, P = 0.629), ORR (OR 1.20, 95% CI 0.58-2.49, P = 0.623), or rate of adverse events (OR 0.82, 95% CI 0.46-1.47, P = 0.510). Conclusion: In this real-world population of patients with unresectable HCC treated with immunotherapy, BB use was not associated with OS, PFS or ORR.